Highly sensitive and fast responding CO sensor based on Co3O4 nanorods - Patil, Dewyani; Patil, Pradip; Subramanian, Vijayanand; Joy, Pattayil Alias; Potdar, Hari S. (Talanta, 2010)
Co3O4 nanorods (diameters similar to 6-8 nm and lengths similar to 20-30 nm) were synthesized for the first time through a simple co-precipitation/digestion method by calcination of cobalt hydroxyl carbonate in air and their CO gas sensing properties were investigated. The Co3O4 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 6.55-50 ppm CO gas at 250 degrees C), extremely rapid response (similar to 3-4s), fast recovery (similar to 5-6s), excellent repeatability, good selectivity and lower operating temperature (similar to 250 degrees C). Furthermore, the Co3O4 nanorods are able to detect up to 5 ppm for CO with reasonable sensitivity (similar to 3.32) at an operating temperature 250 degrees C and they can be reliably used to monitor the concentration of CO over the range (5-50 ppm). The experimental results clearly demonstrate the potential of using the Co3O4 nanorods as sensing material in the fabrication of CO sensors. Plausible CO sensing mechanism of the Co3O4 nanorods is also discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: CO sensor; Co3O4 nanorods; HRTEM; Semiconductor gas sensors; XPS; XRD

Rationally designed CuFe2O4-mesoporous Al2O3 composite towards stable performance of high temperature water-gas shift reaction - Subramanian, Vijayanand; Gnanakumar, Edwin S.; Jeong, Dae-Woon; Han, Won-Bi; Gopinath, Chinnakonda S.; Roh, Hyun-Seog (Chemical Communications, 2013)
High temperature water-gas shift reaction was demonstrated for the first time on a CuFe2O4-mesoporous alumina nanocomposite between 350 and 550 degrees C with 70-80% CO-conversion using simulated waste derived syngas under realistic conditions. Despite high Al-content, the catalyst exhibited stable activity, which was attributed to the nano-architectured robust porous nature of alumina integrated with surrounding CuFe2O4.